2007
DOI: 10.1177/0961203307083175
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity, damage and survival in Mexican patients with acute severe systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a clinical syndrome of varying severity. Although the survival and prognosis of SLE have steadily improved, there is a group of patients who present an acute fatal outcome despite aggressive therapy. We designed this study to evaluate the factors associated with mortality in patients with acute severe SLE. During 2004-06, 41 Mexican SLE patients that could not be managed in the out-patient clinic and with acute severe major organ system involvement [nephritis, severe throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 11 publications
2
25
1
6
Order By: Relevance
“…Interestingly, the lower frequency of at least one major organ involvement (renal, neurological and/or hematological) in patients with either thyroid dysfunction or thyroid autoantibodies supports the notion of a mild disease in this subgroup of patients. Actually, a higher frequency of fatal outcome is associated with severe acute involvement of these organs despite aggressive therapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the lower frequency of at least one major organ involvement (renal, neurological and/or hematological) in patients with either thyroid dysfunction or thyroid autoantibodies supports the notion of a mild disease in this subgroup of patients. Actually, a higher frequency of fatal outcome is associated with severe acute involvement of these organs despite aggressive therapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mexican patients with SLE have an elevated risk of major organ involvement (13). This type of patient usually requires immunosuppressive drugs and even biologic therapy, which may increase the risk of squamous intraepithelial lesions in patients with cervical HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, the increase in the number and the cost of avoidable hospitalizations has been remarkable among SLE patients [2]. Regarding mortality, a Mexican report has revealed a correlation between active lupus nephritis (LN) and infections [3]. A nationwide claim-based study in the USA has found that African Americans have higher mortality due to SLE than Caucasians [4].…”
Section: Introductionmentioning
confidence: 99%